Perencanaan Tangga Wisata Permandian Latamburu di Desa Lamaninggara Kec. Siompu Barat Kab. Buton Selatan - Hajia, Muhammad Chaiddir; Syawal, Syawal; Erdin, Erdin (MANGENTE: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2022)
Lamaninggara Village is ripe for tourism development. This area is home to a number of very strategic and potentially high-value natural tourism assets that must be preserved, developed, and marketed. Among some of these tourist attractions is the Latamburu Baths tourist complex. This resort complex in the southern region attracts the attention of residents both from within and outside the area. Prior to conducting field measurements, the service team will conduct socialization and coordination with the Village Government and local communities to ensure that staircase planning can be carried out properly. The next stage is to make a picture of the staircase structure which can be seen in Figure 1. The problem of access to the Latamburu baths faced by the Lamaninggara Village Government, then there are several solutions offered such as this plan making it easier for villagers who have been experiencing difficulties and this plan helps the village government in the field of planning By following this service, it is hoped that the sub-district government can cooperate with the Faculty of Engineering UM Buton in socialization and training initiatives to improve the performance of the Lamaninggara Government. Keywords: Lamaninggara Village, Stairs, Tourism